ANALISIS ABORSI DALAM PERATURAN PEMERINTAH NO. 61 TAHUN 2014 TENTANG KESEHATAN REPRODUKSI - Ferry Fadzlul Rahman (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2018)
Abortion is a social phenomenon that is increasingly alarming. The concern is not without reason, because so far the behavior of abortion many negative effects both for themselves the perpetrators and the wider community. With the passing of the Government Regulation No. 61 Year 2014 on Reproductive Health still raises the pros and cons in the middle of the community. The approach used to address the problem that the above problems are normative juridical approach. Based on the results of the study need to decriminalize abortion in Government Regulation No. 61 Year 2014 on Reproductive Health which has the goal of creating the legal basis for abortion and the experts who helped him as an indication of a medical emergency or pregnancy due to rape, and factors inhibiting the decriminalization of abortion is legal factors themselves, law enforcement officials factors, factors facilities or infrastructure, community factors, and cultural factors. Suggestion that the author should the government needs to review the Government Regulation No. 61 Year 2014 on Reproductive Health in particular Article 31 and Article 34 within the limited evidence of rape victims in just 40 days because of the time limit is not relative to the law enforcement agencies to prove it, as well as regarding the evidentiary aspects of pregnancy due to rape victims in order to avoid an impression of legitimizing the act of abortion in any form. Keywords: Abortion, , Reproductive Health